ChemInform Abstract: A Direct C—H/Ar—H Coupling Approach to Oxindoles, Thio‐Oxindoles, 3, 4‐Dihydro‐1H‐quinolin‐2‐ones, and 1, 2, 3, 4‐Tetrahydroquinolines. Issue 16 (April 2015) - Hurst, Timothy E.; Gorman, Ryan M.; Drouhin, Pauline; Perry, Alexis; Taylor, Richard J. K.
Abstract CEH is identified as inexpensive and efficient catalyst for all approaches to the title heterocycles including double cyclizations [cf.